The Comparison of the Effectiveness of Fredrickson’s Positive Thinking and Dweck’s Mind Set Program on Test Anxiety of Gifted Students - Zahra Arami; Tayyebeh Sharifi; Ahmad Ghazanfari; Ahmad Abedi; Mohammad Ghasemi pirbaloti (پژوهشنامه روانشناسی مثبت, 2018)
The aim of this study was to investigate the comparison of the effectiveness of Fredrickson’s positive thinking and Dweck’s mindset program on test anxiety of gifted female students in ninth-grade high school in the city of Isfahan.This study is quasi-experimental with pretest-posttest with control group. The population of the study consisted all 450 gifted female students in ninth-grade of Isfahan city, Iran. After screening the student using the Test Anxiety Inventory (TAI), a sample of 45 students who were obtained higher scores were selected and then randomly divided into the experimental group (Fredrickson’s positive thinking and Dweck’s mindset program groups; n=15, for each group) and the control group (n =15). Each of the experimental group were received 8 sessions of intervention, while no intervention for the control group. All participants were completed the TAI at pre-/post-test. Data were analyzed using the MANOVA.The results showed that there was no significant difference between the Fredrickson’s positive thinking group and control group; but there was a significant difference between the Dweck’smindset program group with the Fredrickson’s positive thinking group as well as the control group, so that the Dweck’s mindset group had lower levels of anxiety.The Dweck’s mindset program can decrease anxiety of gifted children, which in turn can increase efficacy and appropriate advancement of these students.